Analisis Model Pembelajaran Discovery Learning dengan Video Tutorial terhadap Minat dan Kreativitas Siswa SMPS Maarif NU 3 Sampang - Muqoffi, Ahmad; Kusmiyati, Kusmiyati; Hanifah, Sri Yuni (Peneliti.net, 2024)
Learning models are created in order to maximize learning activities carried out between teachers and students. The aim of the research is to determine the effect of the Discovery Learning learning model with video tutorials on the interest and creativity of students at SMPS Maarif NU 3 Sampang?. This research uses a quantitative approach and Quasi experimental design. The results of the analysis and explanation based on the data significantly have a correlation relationship of 0.031 <0.05 which is proven in the SPSS output results, then the percentage of correlation relationship is 37.0%. From the data obtained in the field and analyzed and calculated with the help of SPSS, it can be said that the influence of the Discovery Learning learning model with video tutorials on student interest in learning is 13.7%, while the percentage of influence of the Discovery Learning learning model with video tutorials on student creativity is 40.4%. very influential.